2005
DOI: 10.1515/jpm.2005.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fetal breathing movements at 30–38 weeks of gestation

Abstract: The photogrammetric technique revealed differences in some patterns of fetal breathing movements between weeks 30-32, 33-36 and 37-38 of gestation. The data provide a sound basis for relating changes in fetal breathing movements with physiological and anatomical changes that occur as the respiratory system matures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…There are other anatomo‐physiological considerations that need to be taken into consideration when assessing fetal breathing movements, for example, it has been shown that progressive hypoxia and hypercapnia alter the ventilatory responsiveness in low‐birth‐weight lambs13. In humans, it has been shown that the fetal breathing pattern shows changes that are linked to gestational age21, 22. In one of these studies22 it was shown that there is a clear difference in the fetal breathing pattern between 30 and 32 weeks and 33 and 36 weeks' gestation in normal pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other anatomo‐physiological considerations that need to be taken into consideration when assessing fetal breathing movements, for example, it has been shown that progressive hypoxia and hypercapnia alter the ventilatory responsiveness in low‐birth‐weight lambs13. In humans, it has been shown that the fetal breathing pattern shows changes that are linked to gestational age21, 22. In one of these studies22 it was shown that there is a clear difference in the fetal breathing pattern between 30 and 32 weeks and 33 and 36 weeks' gestation in normal pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it has been shown that the fetal breathing pattern shows changes that are linked to gestational age21, 22. In one of these studies22 it was shown that there is a clear difference in the fetal breathing pattern between 30 and 32 weeks and 33 and 36 weeks' gestation in normal pregnancies. Therefore, the design of our research protocol divided the cases into two groups: Group A, which corresponds approximately to the late cannalicular/pre‐alveolar stage, and Group B, which corresponds to the pre‐alveolar/alveolar stage of lung development.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory movements were considered to be present when rhythmic movements of chest wall and diaphragm were observed, in opposition to the abdominal wall, according to techniques already reported 3,6,16 …”
Section: Methodsmentioning
confidence: 99%
“…Respiratory movements were considered to be present when rhythmic movements of chest wall and diaphragm were observed, in opposition to the abdominal wall, according to techniques already reported. 3,6,16 All echocardiograms were recorded on VHS tapes. Considering the already established reproducibility of the technique for Doppler echocardiographic evaluation of pulmonary venous flow indexes, 17 intraobserver and interobserver variabilities were not calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Tada je ustanovljeno da su disajni pokreti ploda epizodični (Boddy et Mantell, 1972). Studije koje su potom usledile su precizirale i opisale obrasce fetalnih respiratornih pokreta u zavisnosti od fizioloških i anatomskih promena koje se dešavaju kako respiratorni sistem sazreva tokom trudnoće (Florido et al, 2005). Kasnijim napretkom ultrazvučne dijagnostike i detaljnijim istraživanjima otkriveno je da su njihove karakteristike promenjene u pojedinim stanjima i oboljenjima.…”
Section: 2e Intenzivirani Fetalni Disajni Pokretiunclassified